Pengaruh Employee Engagement dan Kemampuan Kerja Terhadap Produktivitas Karyawan Pada BPR Bank Buleleng 45 Kantor Kas Seririt di Bali - I Putu Hery Kapriawan; Ni Ketut Murdani; Ni Luh Indiani (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
The purpose of this research is to determine the effect of employee engagement on work ability on employee productivity. The research objects used in this research are employees at BPR Bank Buleleng 45 Senirit Cash Office in Bali. The method used in this research is a quantitative descriptive method with data collection instruments in the form of questionnaire. Statistical data analysis (SPSS) to test the hypothesis that has been proposed. The results of this research are 1) employee engagementpositive and significant effect on employee productivity with t value >1 table = 2.524 1.071 sig=0.015; 2) work ability has a positive and significant effect on employee productivity with a calculated t value > t table = 5.062 >1.071 sig=0.000.3) employee engagement and work ability simultaneously hasp an effect on employee productivity with the calculated F value-73.685 and a significant value of 0.000.